The ‘Absolute Colour Music’ of Jan van Deene - Ludo van Halem (The Rijksmuseum Bulletin, 2023)
Ludo van Halem discusses the work of De Onafhankelijken, a group of painters who introduced the first abstract art in the Netherlands. They were reviled in the press, and their contribution was only recognized late. For example, Jan van Deene's Peinture VII (1913) was only included in the Rijksmuseum collection in 2019.